The Role of Parents in Preventing Children from Being Addicted to Playing Gadgets in Kuyanga I Village, North Tombatu District, Southeast Minahasa Regency - Melenia Alow; Yoseph D.A. Santie; Veronike E.T Salem (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JELAS), 2024)
The aim of this study is to learn more deeply about the role of parents in preventing children from being addicted to playing gadgets in Kuyanga I Village, North Tombatu District, Southeast Minahasa Regency. In achieving the research objectives, qualitative research methods are chosen, with data collection methods such as observations and interviews. The results of the research show that has been carried out, the conclusions from the results of this research are the role of parents is to look after, protect and finance in preventing children from playing with gadgets, which is very important, where gadgets, apart from having a positive impact, can also have a negative impact on children whose use is not controlled by each parent. Apart from being mentally damaging, it can also affect children's health. So apart from limiting how they use gadgets, parents must also be wise in giving cellphones to their children so that they don't waste their time just playing with gadgets but also invite children to play together at home.